9B.06: COMPARISON BETWEEN ALDOSTERONE AND RENIN MEASUREMENT BY CHEMILUMINESCENT IMMUNOASSAY AND RADIOIMMUNOASSAY FOR THE DIAGNOSIS OF PRIMARY ALDOSTERONISM. (June 2015) - Burrello, J.; Buffolo, F.; Monticone, S.; Viola, A.; Falcetta, A.; Lucchiari, M.; Mengozzi, G.; Rabbia, F.; Veglio, F.; Mulatero, P.
Abstract : Objective: Primary aldosteronism (PA) is the most frequent cause of secondary hypertension responsible for an increased rate of cardiovascular events. According to the Endocrine Society Guidelines, up to 50% of hypertensive patients should be screened for PA, using the aldosterone to renin (or plasma renin activity, PRA) ratio (AARR and ARR, respectively). The automated Diasorin LIAISON® chemiluminescent immunoassay for renin and aldosterone measurement became available and in many laboratories is currently used instead of the classical radioimmunometric PRA and aldosterone assay. Aim of the study was to prospectively compare the diagnostic accuracy of AARR and ARR as screening test for PA and the two aldosterone assays also during confirmatory test in patients with a positive screening test. Design and method: One hundred patients were screened for PA and 44 patients underwent confirmatory test (either by intravenous saline load or by captopril challenge test). We considered as cut off for the AARR 2.7 (ng/dL/mU/L) and for the ARR 30 (ng/dL/ng/mL/h). All patients positive to one of the two screening test underwent confirmatory test; patients with positive confirmatory test underwent subtype diagnosis by CT scanning and adrenal vein sampling. Results: Seventy three patients were diagnosed as essential hypertensives, 22 had bilateral adrenal hyperplasia and 5 had an aldosterone producing adenomas (APA). The AARR displayed a sensitivity of 78% and a specificity of 100%, whereas the ARR had a sensitivity of 96% and a specificity of 90%. Of the 6/27 PA patients missed by AARR, none resulted to be affected by APA. All PA patients were correctly diagnosed by chemiluminescence at confirmatory test. In the overall sample of 181 measurements available both the correlation for the PRA with renin and for aldosterone in chemiluminescence and radioimmunoassay were highly significant (Rho = 0.66, p < 0.0001 and Rho = 0.80, p < 0.0001, respectively). On ROC curves, the AUC for AARR was 0.905 (95% CI 0.821-0.988) and for ARR 0.947 (95% CI 0.903–0.991) and they were not significantly different. Conclusions: The automated aldosterone and renin chemiluminescent assay is a reliable alternative to the well-established radioimmunometric method, especially for the detection of APA.